PERAN DESAIN GRAFIS BERBASIS AI DALAM PENYAMPAIAN PESAN DAKWAH DI MEDIA SOSIAL - Ilham; Razak Al Hamsi Sirait; Nur Hasanah; Cahaya Ariska Sitompul; Suci Rahmitha (AT-TAWASUL, 2026)
The development of da'wah in the digital era has brought significant changes in the methods and strategies of delivering religious messages. This study analyzes the transformation of digital da'wah, the role of social media as a space for visual da'wah, and the contribution of AI-based graphic design in supporting the effectiveness of da'wah communication. The results show that digitalization has expanded the reach of da'wah through platforms like Instagram, YouTube, TikTok, and Facebook, allowing messages to be disseminated quickly, widely, and interactively. Da'wah is no longer limited to physical spaces but has evolved into a creative, adaptive virtual activity that can be accessed anytime. AI-based graphic design plays an important role in supporting the presentation of visual da'wah. AI technology can automate the design process, generate modern visuals, and maintain aesthetic consistency, making it easier for preachers and content creators to produce high-quality da'wah materials. AI characteristics such as automation, generative capabilities, precision, and personalization enable da'wah messages to be delivered in an engaging, concise, and easily understood manner for the digital community, especially the younger generation. Meanwhile, social media serves as a strategic visual da'wah space, facilitating the dissemination of content based on images, videos, infographics, and illustrations. Visualization has been proven to increase the appeal and effectiveness of messages, while also opening up two-way communication between the preacher and the audience. However, this development also presents challenges, such as the risk of religious misinformation, commercialization of da'wah, and dependency on AI technology. Overall, the integration of digital da'wah, social media, and AI-based graphic design provides great opportunities for spreading Islamic values in a more creative, effective, and relevant way to the communication style of modern society. With wise utilization based on Sharia values, technology can become an important means to strengthen preaching that is informative, inclusive, and a mercy to all worlds